Efficient Chromosome Doubling of an Interspecific Hybrid Dendrobium Stardust 'Fire Bird' by Treatment of Amiprofos-methyl to Protocorm-Like Body - Kondo, Haruka; Phlaetita, Wasana; Mii, Masahiro; Kikuchi, Shinji; Deguchi, Ayumi; Miyoshi, Kazumitsu (In vitro cellular & developmental biology. Plant, 2020)
Dendrobium Stardust 'Fire Bird' is an interspecific hybrid between D. unicum and D. Ukon 'Arai' and is known to be sterile and prevents further breeding. Chromosome doubling is an essential method to increase the size of plant organs, such as flowers, and restore fertility of interspecific hybrids, which enables further breeding for ornamental traits. To induce chromosome doubling, the protocorm-like bodies (PLBs) of a given variety were treated in vitro for 6 to 48 h with 10 to 160 mg L⁻¹ amiprofos-methyl (APM). Higher concentrations resulted in lower rates of survival of treated PLBs. Furthermore, subsequent growth of PLBs was hampered with prolonged APM treatment, although 10 and 20 mg L⁻¹ APM was optimal for doubling chromosomes. Plantlets with a swollen and shorter stem were observed after the APM treatment and these plants were also chromosome-doubled and became a distinctive morphological marker for the primary selection of chromosome-doubled plants. Chromosomedoubled plants of D. Stardust 'Fire Bird' will be utilized for the future breeding of unique Dendrobium cultivars.